Development of lycopene-loaded nanostructured lipid carriers: Effect of rice oil and cholesterol - P. Riangjanapatee (2018)
Nanostructured lipid carriers (NLC) were developed using a skin-compatible surfactant and natural lipid materials (rice oil, cholesterol) to incorporate lycopene. Characteristics of the NLC were explored in comparison with nanoemulsions and solid-lipid nanoparticles (SLN). Photon correlation spectroscopy, laser diffractometry (LD) and differential scanning calorimetry were used to determine particle size and thermal stability. Particle size expressed as LD (0.99) was 405nm for the SLN, 350nm for the NLC without cholesterol and 287nm for the NLC with cholesterol. Rice oil and cholesterol enabled the formation of smaller particles, but cholesterol also reduced drug stability in the NLC. To preserve chemical stability of lycopene in the NLC, cholesterol should be avoided and storage should be at 4 °C or at room temperature.